(untitled) (Research, Society and Development, 2020)
This study presents an excerpt from a master’s dissertation with the objective of to investigate the contributions of pedagogical strategies in the discipline of Supervised Curricular Internship (ECS) for the training of nursing students. This is a qualitative research in the form of bibliographic review of the narrative type, with the search for articles carried out through the Virtual Health Library (VHL). Articles published between 2009 and 2019, in Portuguese, English and Spanish, were included. Thus, it resulted in the selection of 13 articles to compose the study, from which two thematic categories emerged. The findings go through the positive changes provided by the standardization and mandatory nature of the ECS, the teacher-student relationship as a tool for the safety and success of the teaching process. In addition, the contribution of ECS to the development of skills and competences of nursing students is highlighted. From the data obtained, it was concluded that the approximation between service, teaching institution and teacher is fundamental to the teaching-learning process at ECS. Furthermore, students need teaching strategies that stimulate them during the ECS discipline.